The Significance of Studying the Subject "Atomic Structure and Chemical Bonding" in Physics and Chemistry in Higher Education Institutions - Bakhodir Abdusamatovich Mirsalikhov; Yavkacheva Zulxumor Abdurasulovna; Saytdjanov Shovkat Nigmatjanovich (Scientific Trends, 2024)
This article highlights the importance of teaching students physics and chemistry because of the disconnect between theory and practice in the interdisciplinary study of the atom and atomic nucleus. In addition, the experiences of scientists in the fields of physics and chemistry are analyzed, and the relevance of the application of atomic structure and chemical bonding to students in physics and chemistry is explained in detail.
Keywords: physics, chemistry, matter, particle, electrolysis, atom, nucleus, electron, proton, neutron, radioactive, spin, bond, electron cloud, electronic configuration.